Advances in Vibration Engineering and Structural Dynamics - Beltran-Carbajal, Francisco (IntechOpen, 2012)
The aim of this book is to present recent and innovative advances on research studies and engineering applications in important areas of vibration engineering and structural dynamics. The fourteen chapters of the book cover a wide range of interesting issues related to modelling, rotordynamics, vibration control, estimation and identification, modal analysis, dynamic structures, finite element analysis, numerical methods and other practical engineering applications and theoretical developments on this very broad matter. The audience of the book includes researchers, professors, engineers, practitioners, engineering students and new comers in a variety of disciplines seeking to know more about the state of the art, challenging open problems and innovative solution proposals in vibration engineering and structural dynamics.